Role of Regulatory Oncogenic or Tumor Suppressor miRNAs of PI3K/AKT Signaling Axis in the Pathogenesis of Colorectal Cancer - Soleimani, Atena; Rahmani, Farzad; Ferns, Gordon A.; Ryzhikov, Mikhail; Avan, Amir; Hassanian, Seyed M. (Current Pharmaceutical Design, 2018)
Colorectal cancer (CRC) is the leading cause of cancer death worldwide and its incidence is increasing. In most patients with CRC, the PI3K/AKT signaling axis is over-activated. Regulatory oncogenic or tumor suppressor microRNAs (miRNAs) for PI3K/AKT signaling regulate cell proliferation, migration, invasion, angiogenesis, as well as resistance to chemo-/radio-therapy in colorectal cancer tumor tissues. Thus, regulatory miRNAs of PI3K/AKT/mTOR signaling represent novel biomarkers for new patient diagnosis and obtaining clinically invaluable information from post-treatment CRC patients for improving therapeutic strategies. This review summarizes the current knowledge of miRNAs’ regulatory roles of PI3K/AKT signaling in CRC pathogenesis.
Keywords: microRNAs